Electric Dreams: Understanding Factors Shaping EV Purchase Intentions And Policy Implications - Adzania, Fajriah Hanika; Candra, Halbet Dermawan; Susanti, Rahayu Fajri; Setiowati, Rini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The shift towards electric vehicles (EVs) signifies a substantial transformation in automotive technology and consumer preferences. This study investigates the multifaceted factors influencing Indonesian consumers' purchase intentions towards EVs by integrating the Theory of Planned Behavior (TPB) with additional variables: Environmental Knowledge (EK), Intolerance of Uncertainty (IoU), and Financial Incentive Policies (FIP). Employing a quantitative approach, data from 220 respondents were collected through an online survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings indicate that Attitude (AT), Subjective Norms (SN), FIP, and EK significantly and positively correlate with Purchase Intention (PI), while Perceived Behavioral Control (PBC) exerts no significant influence. Conversely, IoU demonstrates a significant negative association with PI. Furthermore, AT mediates the relationships between EK, IoU, and PI. These insights offer valuable contributions to academic discourse and provide practical guidance for policymakers, marketers, and industry stakeholders seeking to accelerate EV adoption through informed strategies and supportive policies.